Regular Multivitamin Supplement Use, Single Nucleotide Polymorphisms in ATIC, SHMT2, and SLC46A1, and Risk of Ovarian Carcinoma - Kelemen, Linda E.; Wang, Qinggang; Dinu, Irina; Vierkant, Robert A.; Tsai, Ya-Yu; Cunningham, Julie M.; Phelan, Cathy M.; Fridley, Brooke L.; Amankwah, Ernest; Iversen, Edwin S.; Berchuck, Andrew; Schildkraut, Joellen M.; et al. (Frontiers in Genetics, 2012)
ATIC, SHMT2 and SLC46A1 have essential roles in one-carbon (1-C) transfer. The authors examined whether associations between ovarian carcinoma and 15 variants in these genes are modified by regular multivitamin use, a source of 1-C donors, among Caucasian participants from two U.S. case control studies. Using a phased study design, variant-by-multivitamin interactions were tested, and associations between variants and ovarian carcinoma were reported stratified by multivitamin supplement use. Per-allele risk associations were modified by multivitamin use at six variants among 655 cases and 920 controls (Phase 1). In a larger sample of 968 cases and 1,265 controls (Phases 1 and 2), interactions were significant (P≤0.03) for two variants, particularly among regular multivitamin users: ATIC rs7586969 (odds ratio [OR]=0.7, 95% confidence interval [CI]=0.6-0.9) and ATIC rs16853834 (OR=1.5, 95% CI=1.1-2.0). The two ATIC SNPs did not share the same haplotype; however, the haplotypes they comprised mirrored their SNP risk associations among regular multivitamin supplement users. A multi-variant analysis was also performed by comparing the observed likelihood ratio test statistic from adjusted models with and without the two ATIC variant-by-multivitamin interaction terms with a null distribution of test statistics generated by permuting case status 10,000 times. The corresponding observed P value of 0.001 was more extreme than the permutation-derived P value of 0.009, suggesting rejection of the null hypothesis of no association. In summary, there is little statistical evidence that the 15 variants are independently associated with risk of ovarian carcinoma. However, the statistical interaction of ATIC variants with regular multivitamin intake, when evaluated at both the SNP and gene level, may support these findings as relevant to ovarian health and disease processes.